2013
DOI: 10.1371/journal.pone.0056234
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Selectively Increases Protein Degradation and Enhances Prostate Cancer-Specific Apoptosis: Possible Role for Inhibition of Deubiquitinase Activity

Abstract: Inhibition of the ubiquitin-proteasome system (UPS) of protein degradation is a valid anti-cancer strategy and has led to the approval of bortezomib for the treatment of multiple myeloma. However, the alternative approach of enhancing the degradation of oncoproteins that are frequently overexpressed in cancers is less developed. Betulinic acid (BA) is a plant-derived small molecule that can increase apoptosis specifically in cancer but not in normal cells, making it an attractive anti-cancer agent. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 46 publications
4
73
0
Order By: Relevance
“…4). BA is a pentacyclic triterpenoid that was first isolated from the stem bark of Zizyphus mauritiana in 1995 and has been demonstrated to induce apoptosis in various cancer cells including breast, colon, lung, melanoma, neuroblastoma, prostate and leukaemia in vitro and in vivo (Damle et al, 2013;Reiner et al, 2013;Sun et al, 2013;Mertens-Talcott et al, 2012;Kessler et al, 2007;Tan et al, 2003;Pisha et al, 1995). A study reported that BA up-regulated p53 and p21 in MCF-7 cells (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…4). BA is a pentacyclic triterpenoid that was first isolated from the stem bark of Zizyphus mauritiana in 1995 and has been demonstrated to induce apoptosis in various cancer cells including breast, colon, lung, melanoma, neuroblastoma, prostate and leukaemia in vitro and in vivo (Damle et al, 2013;Reiner et al, 2013;Sun et al, 2013;Mertens-Talcott et al, 2012;Kessler et al, 2007;Tan et al, 2003;Pisha et al, 1995). A study reported that BA up-regulated p53 and p21 in MCF-7 cells (Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, overexpression of PA28g was shown to recover proteasome function in an in vitro model of Huntington disease and improve cell viability 15 . Pharmacological agents that enhance UPS activity, however, are extremely rare: oleuropein was shown to enhance all three proteasome peptidase activities in fibroblasts 11 , while betulinic acid activates preferentially the chymotrypsin-like proteasome activity 9 and displays potentially anti-cancer properties 10,45 . Inhibition of the deubiquitinating enzyme USP14 was shown to enhance degradation of oxidized proteins, thereby protecting from oxidative stress 12 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pharmacological agents that increase UPS activity remain largely unexplored [9][10][11][12] , although this mode of regulation has great potential to ameliorate the phenotypes associated with the development of protein deposition diseases, such as Parkinson's 13,14 and Huntington's 15,16 . There is evidence that proteasome activity could be upregulated by overexpressing proteasomal subunits 15,17,18 , increasing E3 ligase expression [19][20][21] and modulating the rates of proteasomal conformational changes that are rate limiting for peptidase activity 22,23 .…”
mentioning
confidence: 99%
“…Curcusone D shares no structural or chemical resemblance to any known DUB inhibitors [19][20][21][22][23][24] despite its ability to inhibit the activities of many cellular DUBs (Fig. 4C), establishing it as a new, partially selective DUB inhibitor.…”
Section: Curcusone D Induces Ros Which Are Required For the Inhibitimentioning
confidence: 99%